Effect of Information and Communication Technology Usage on Service Delivery in Hotel Industries in Abeokuta Metropolis of Ogun State, Nigeria - Olugbemi, M. T.; Ogungbayi, G. B.; Onasanya, A. S. (NIU Journal of Humanities, 2020)
Coping with the complex and dynamic business environments, hotel industry requires adoption and implementation of technologies with the aim of improving service delivery. This paper assessed the effect of Information and Communication technology usage on service delivery in hotel industries in Abeokuta Metropolis of Ogun State, Nigeria. Simple random sampling technique was used to select 215 members of staff from selected hotels. Primary data were collected with the aid of questionnaire analyzed using descriptive statistics such as percentage, mean and frequency. The research also discovered that respondent frequently used electronic lock for safety and security. In addition smoke detector, carbon monoxide, detector and sprinkler system were all available in the hotels for safety in case of fire incidence. Likewise, ICT infrastructure: DSTV, Wi-Fi and intercom were found in all hotels within the sample area. The study found that   ICT helps in wide coverage, attracts international and domestic clients, and quick management decision which invariably improve service delivery. Based on empirical result, the study concluded that high cost of ICT gadgets, internet fraudster, tax on imported ICT spare parts and problem of privacy are factors affecting effective use of ICT among the respondents in the study area.  It is therefore recommended that, government should reduce tax on imported ICT infrastructures and also hotel management must secure their information on internet against privacy and internet fraudsters. Keywords: Information Communication Technology (ICT), Hotel, Service delivery, Customer